Effects of Acupuncture on Neurological Disease in Clinical- and Animal-Based Research - Guo, Xiangyu; Ma, Tao (Frontiers in Integrative Neuroscience, 2019)
Neurological disease, including Alzheimer’s disease (AD), Parkinson’s disease (PD), which were caused by abnormalities in the nervous system, involves the accumulation of false proteins, neurotransmitter abnormalities, neuronal apoptosis, etc. As an alternative supplementary medicine (ASM), acupuncture plays an important role in the treatment of neurological diseases. In this review, we summarized the current evidence for the treatment efficacy of acupuncture in AD and PD from the perspective of clinical trials and animal model. Acupuncture can inhibit the accumulation of toxic proteins in neurological diseases, modulate energy supply based on glucose metabolism, depress neuronal apoptosis, etc., and exert a wide range of neuroprotective effects.